Breeding success and conservation of Eretmochelys imbricata in the Delta do Parnaíba Environmental Protection Area, northeastern Brazil - Neto Pinto Nascimento, Manoel (2021)
Sea turtles are one the most threatened group worldwide mainly due to environmental disturbances caused by anthropogenic actions. Herein, we aimed to investigate the breeding success of hawksbill turtles in two beaches of Piauí state, contained within the Delta do Parnaíba Environmental Protection Area. Turtle nests were monitored according to the methodology proposed by Projeto TAMAR-ICMBio. A multi-model inference approach using Akaike’s Information Criterion (AICc) obtained through the Generalized linear models (GLM) was used to investigate what are the best predictors of hawksbill turtles’ breeding success. We observed that vegetation distance is the main driver of its breeding success (each nest survival rate), reinforcing the needed to preserve the natural vegetation cover existing in coastal environments. With our constant monitoring of nests avoiding predatory attacks, it was allowed the protection of almost four thousand eggs and the consequent liberation of more than three thousand live hatchlings. Therefore, we think that studies, as presented here, are important for the maintenance and conservation of marine turtle populations and, in particular, to subsidize the protection and conservation of hawksbill turtles in the Parnaíba River Delta.